2012
DOI: 10.1097/hjh.0b013e328357c0c9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in circulating concentrations of soluble fms-like tyrosine kinase-1 and placental growth factor measured by automated electrochemiluminescence immunoassays methods are predictors of preeclampsia

Abstract: Changes in circulating concentrations of PlGF, sFlt-1, and in the sFlt-1/PlGF ratio precede the onset of preeclampsia. The risk profile of circulating angiogenic factors for developing preeclampsia distinctly evolves depending on whether this condition is manifested at preterm or term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 31 publications
5
29
0
1
Order By: Relevance
“…We have recently reported that altered placental long-chain polyunsaturated fatty acids may alter the membrane lipid fatty acid composition, leading to the increased release of sFlt-1 in circulation; furthermore, we have also discussed the possibility that the maternal sFlt-1/PlGF ratio may be predictive of PE. 15,41 This is in line with findings reported in recent studies 22,42 but is in contrast to other studies indicating that in early pregnancy, this ratio is not useful for the prediction of PE. 20 The cord plasma VEGF levels in this study were lower in women with PE compared with normotensive women and this supports the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…We have recently reported that altered placental long-chain polyunsaturated fatty acids may alter the membrane lipid fatty acid composition, leading to the increased release of sFlt-1 in circulation; furthermore, we have also discussed the possibility that the maternal sFlt-1/PlGF ratio may be predictive of PE. 15,41 This is in line with findings reported in recent studies 22,42 but is in contrast to other studies indicating that in early pregnancy, this ratio is not useful for the prediction of PE. 20 The cord plasma VEGF levels in this study were lower in women with PE compared with normotensive women and this supports the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with previous reports and provide further support to the notion that alterations of these angiogenic factors not only do occur in women with preeclampsia but also that these biochemical abnormalities become more pronounced as the severity of the disease increases, particularly when preeclampsia occurs preterm. [5][6][7][8] We also showed that higher urinary PRL levels and ALT indicates alanine amino transferase; AST, aspartate amino transferase; LDH, lactate deshydrogensase; PlGF, placental growth factor; PRL, prolactin; sEng, soluble endoglin; and sFlt-1, soluble fms-tyrosine kimase-1. P value is given only for significant differences: *vs women with mild preeclampsia or †vs women with severe preeclampsia after application of appropriate statistical tests.…”
Section: Discussionmentioning
confidence: 75%
“…4,5 Higher circulating concentrations of soluble vascular endothelial growth factor receptor-1 (also referred as soluble fms-like tyrosine kinase-1 [sFlt-1]) and soluble endoglin (sEng), and lower concentrations of placental growth factor (PlGF), are present at the time of diagnosis of preeclampsia and have been associated with an elevated risk to develop this condition for several weeks before the onset of the clinical manifestations. [5][6][7][8] On the other hand, prolactin (PRL), which is physiologically elevated during normal pregnancy, has many effects beyond reproduction and lactation, including an eminent role in angiogenesis and antiangiogenesis. [9][10][11] The major circulating PRL isoform is a 23-kDa single-chain polypeptide (monomeric PRL), which comprises up to 90% of total PRL.…”
mentioning
confidence: 99%
“…This finding suggests that sFlt-1 may be a good marker for earlyonset PE. Previous studies have supported the hypothesis that an earlier onset of PE corresponds with higher sFlt-1 levels [26,27]. However, there are still some discrepancies in the reported sFlt-1 protein levels between studies.…”
Section: Discussionmentioning
confidence: 89%